PROGRAMMED CORRECTIVE EXERCISES IN PCYSICAL EDUCATION CLASSES AND LORDOTIC BAD BODY POSITION - Zoran Bogdanović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2008)
The subject matter of the research was the influence of specially program medphysical education instruction with specific complexes of exercises of corrective gymnastics at the 5th grade pupils at those with lordotic bad body position established by measuring. The aims were to define the number of children with lordotic bad body position and to eliminate or alleviate the existing disturbance until the end of the experimental programme. The experimental programme was carried out among the 5th grade pupils. Total number of pupils included in this experiment was 434. The methods that were used for the estimation of lordotic bad body position are somatoscopy and somatometry. The plumb, ruler and dermograph were necessary instruments. For the estimation of the states of bad body position, the average value of mild criterion is applied. It can be concluded that during experimental programme even 85.93% of the subjects successfully corrected their bad body position; more exactly completely corrected lordotic bad body position. That percentage is certificate of justification and necessity of application of experimental programme of corrective gymnastics with all his organizational characteristics (the setting, the scope of work, load intensity, directing and controlling the experiment). Muscular-bone system of boys shows the high level of adaptation on the applied experimental factor of corrective gymnastics.